Expression and structural-functional alterations of α-1-acid glycoprotein at the pathological state - Stekleneva, N.I.; Shevtsova, A.I.; Brazaluk, O.Z.; Kulinich, A.O. (Вiopolymers and Cell, 2010)
The review analyzes up-to-date knowledge on structure and biological functions of α-acid glycoprotein. A special attention is given to alterations in fucosylation, sialylation and branching of orosomucoid at the acute, chronic inflammation and oncotrans formations. Проаналізовано сучасні дані щодо структури і біологічних функцій α-1-кислого глікопротеїну. Особливу увагу приділено зміні фукозильованості, сіальованості і розгалуженості гліканів орозомукоїду за гострого і хронічного запалення та онкотрансформації. Проанализированы современные данные, касающиеся структуры и биологических функций α-1-кислого гликопротеина. Особое внимание уделено изменению фукозилированности, сиалированности и разветвленности гликанов орозомукоида при остром и хроническом воспалении, а также онкотранс- формации.